Study on the antagonistic mechanism of some selected fluorescent Pseudomonas strains toward Fusarium oxysporum - Tuyet Nhung, Nguyen Thi; Anh, Nguyen Minh; Hoai Anh, Phan Thi; Dung, Nguyen Ngoc (Academia Journal of Biology, 2014)
The presence of antifungal agents in 7 selected fluorescent Pseudomonas strains were tested. The obtained results showed that none of them was able to decompose chitin, laminarin and cellulose, but capable to use skim milk. All strains could produce siderophores and cyanid, but there was a difference among them. Only the P. fluorescens strain Ps7-1 showed the presence of phlD, one of 4 genes coding 2,4-Diacetylphloroglucinol. With such results, it could be suggested that the antagonism of some selected fluorescent Pseudomonas strains toward F. oxysporum might be a combination of more than one mechanism.